Systematics of cetaceans using restriction site mapping of mitochondrial DNA - Ohland, Derek Paul (Division of Chemical Pathology, 2018)
A phylogenetic study of eleven cetaceans was undertaken using Restriction Endonuclease Maps (RSM) of mitochondrial DNA (mtDNA). One species from the suborder mysticeti (baleen whales) was sampled, and of the ten odontocetes (toothed whales) sampled two were from the family Ziphiidae (beaked whales) and eight were from the family Delphinidae (dolphins) (each representing a different genus). The primarily opportunistically obtained (i.e. from strandings or accidental death in commercial trawl nets) heart tissue generally yielded high quantities of mtDNA which is needed for double digest fragment analysis. The mtDNA extracted from the sampled taxa was cleaved with fifteen different six-base Restriction Enzymes (RE's). Using the three-way method of analysis and aided by the computer program Resolve (Ver. 2.7) (Harley, unpublished), RSM's were constructed. Distance (Neighbor-Joining and Fitsch-Margoliash) and cladistic (Maximum Parsimony and Bootstrap) methods were used to infer phylogenies. The baleen whale was used as an outgroup for the cladistic analysis. Both the distance and both the cladistic methods produced the same single topology, which is concordant with morphologically based classifications. The two differences (within the Delphinidae), viz. Grampus' most basally rooted position and Cephalorhynchus' grouping with the Delphininae are of taxa whose groupings are unresolved in the morphologically based classifications. Using Brown et al's (1979) molecular clock, very recent divergence times at the generic, family and suborder levels were obtained, when compared to fossil based estimates. Using the odontoceti/mysticeti split the base substitution rate of cetacean mtDNA was estimated to be much slower than that of terrestrial mammals (0,3% compared to 1,0% Myr⁻¹). A similarly slow rate was calculated for cetacean nuclear DNA (nDNA) (0,09% Myr⁻¹) (Schlotterer et al, 1991). It remains an unresolved issue as to whether the base substitution rate of cetacean DNA is slower than terrestrial mammals or whether the fossil evidence needs to be reinterpreted. The time of the mysticeti/odontoceti split is palaeontologically uncertain and the suggested monophyletic status of the extant suborders has been questioned, thus making the calculation of cetacean base substitution rate risky. Equally, the incomplete fossil record can lend itself to misinterpretation.